Gambaran Kepuasan Pasien Asuransi Inhealth Tentang Pelayanan Kefarmasian Di Apotek Kimia Farma 387 Pondok Gede Jawa BaratPeriode Februari-April 2025 - Dessy Adelia Pramesty; Guruh Subagya; Sindi Astuti (Jurnal Ilmu Farmasi Terapan dan Kesehatan, 2025)
Patient satisfaction is an important indicator in assessing the quality of pharmaceutical services. This study aims to describe the level of patient satisfaction of Mandiri Inhealth insurance users at Kimia Farma Pharmacy 387 Pondok Gede. The research method used a quantitative descriptive approach with a purposive sampling technique, involving 223 respondents from a total of 504 patients for the period February–April 2025. Data collection was carried out through a questionnaire that had been tested for validity (r> 0.361) and reliability (α = 0.960). The results showed that based on the SERVQUAL model, the highest level of satisfaction was found in the dimensions of responsiveness (64% very satisfied) and reliability (62% very satisfied), followed by empathy (59%), assurance (47%), and real (40%). Overall, 54% of respondents stated very satisfied, 40% satisfied, 5% quite satisfied, and 1% dissatisfied. Although the majority of patients were satisfied, this achievement fell short of the 100% target for the Kimia Farma Pharmacy Patient Satisfaction Index (PIKP). This finding indicates the need for service quality improvements, particularly in tangible and guaranteed dimensions, such as providing more adequate facilities and improving staff competency. This study provides recommendations for continuous improvement to achieve optimal service standards.